Why ’one size fits all’ concept and policies of inclusive education is insufficient to achieve ‘true’ inclusivity in a national context: Insight from a tablet based disaster preparedness training programme administered in Bangladesh - Tarek, Syed Ali (Proceedings of the International Conference on Networked Learning, 2016)
In today’s world, education is a basic human right and it is desired that every human being regardless of his or her personal and societal circumstances should get a fair chance to get access to education. ‘Inclusive education’ as a concept exists since the mid 19th century which was later translated into various international policy frameworks. Often these international policies had a push impact towards national policy agendas. Majority of the nations that adopted those international policies were hardly successful in achieving ‘inclusive’ learning practices, as because, ‘inclusivity’ has various wider (local) aspects which needs to be considered. A chronological review of relevant international policies and Bangladesh government’s policies is presented in the early segments and then shortfalls of current notions of inclusivity is explored in this paper. A brief overview is given based on the author’s experience of running a tablet based disaster preparedness training in Bangladesh over three years’ period, that used networked learning concepts to promote ‘inclusivity’. This paper also explores, how the training programme needed to broaden its perspectives to accommodate inclusivity. It was found during the training that the current notion and understanding of the term relates to only a fragment of the people to which inclusivity should be aimed. Adult learners are in a disadvantageous position as the national policies hardly mention their needs. Within a group of policies aimed to serve (special) children in education, practitioners are ill informed to support adult learners’ in formal, informal and non-formal education sector. Reports on outcome of the alternate education systems consisting of private education and NGO led training in Bangladesh noted that there is a high level of drop outs those who attend any form of training. Majority of the participants lack awareness and urges to learn about something new. Due to monotonous delivery standards the participants are disengaged quickly with the feeling that they have no voice in their learning experience. The participants crave for a system which would acknowledge and value their experience and bridge those experiences to construct something more useful. The disaster preparedness training thus had to adapt to these less explored inclusivity issues to ensure, there is a true wider ‘inclusive’ participation. This paper reinforces that, there is a need to understand the varied needs of the adult learners to ensure they are well integrated in any format of the education system, especially where cooperative learning takes place.